Molecular mechanism of organotin toxicity via nuclear receptor signaling - Nakanishi, Tsuyoshi (Biomedical Research on Trace Elements, 2011)
Organotin compounds have been widely used as antifouling biocides for ships and fishing nets, agricultural fungicides and rodent repellents. These widespread uses have resulted in the release of increasing amounts of organotins into the environment. In aquatic invertebrates, particularly marine gastropods, organotin compounds, such as tributyltin (TBT) and triphenyltin (TPT), induce irreversible sexual abnormality in females which is termed "imposex" at very low concentrations. Although it has been theorized that these compounds act as potential competitive inhibitors of aromatase, which converts androgen to estrogen, and then increase levels of unconverted androgens in gastropods, their effective concentrations for aromatase inhibition are high. In addition to wildlife, organotins may have various undesirable effects on human health. Contrary to the theory of organotin-induced aromatase inhibition in gastropods, in human choriocarcinoma cells, these compounds markedly enhance estradiol biosynthesis along with the increase of both aromatase activity and 17β-hydroxysteroid dehydrogenase type I (17β-HSD I) activity, which converts low-activity estrogen estrone to the biologically more active form estradiol, at the same low concentrations. Although there are many reports describing the potential toxicity of organotins in human and mammals, the critical target molecules for the toxicity of organotin compounds remain unclear. Recently, organotin compounds including TBT and TPT were identified as nanomolar agonists for retinoid X receptor (RXR) and peroxisome proliferator-activated receptor (PPAR) γ, which are members of the nuclear receptor superfamily. Here, we review the potential genetics action and subsequent toxicity induced by organotins via these nuclear receptors.